Do Marketers Matter for Entrepreneurs? Evidence from a Field Experiment in Uganda. (May 2021) - Anderson, Stephen J.; Chintagunta, Pradeep; Germann, Frank; Vilcassim, Naufel
Promoting growth by differentiating products is a core tenet of marketing. However, establishing and quantifying marketing's causal impact on firm growth, while critical, can be difficult. This article examines the effects of a business support intervention in which international professionals from different functional backgrounds (e.g., marketing, consulting) volunteered time to help Ugandan entrepreneurs improve growth. Findings from a multiyear field experiment show that entrepreneurs who were randomly matched with volunteer marketers significantly increased firm growth: on average, monthly sales grew by 51.7%, monthly profits improved by 35.8%, total assets increased by 31.0%, and number of paid employees rose by 23.8%. A linguistic analysis of interactions between volunteers and entrepreneurs indicates that the marketers spent more time on product-related topics than other volunteers. Further mechanism analyses indicate that the marketers helped the entrepreneurs focus on premium products to differentiate in the marketplace. In line with the study's process evidence, firms with greater market knowledge or resource availability benefited significantly more than their peers when matched with volunteer marketers. As small-scale businesses form the commercial backbone of most emerging markets, their performance and development are critically important. Marketers' positive impact on these businesses highlights the need for the field's increased presence in emerging markets.